Housing subsidy as a tool of targeted financial assistance to the population (Economics and region, 2022)
The paper studies the peculiarities of the application of the housing subsidy as a tool of targeted financial assistance to the population. It was found that housing subsidies are understood as an effective social tool for providing free targeted assistance to households from the state, which provides an opportunity to direct it to those households that actually need to receive state assistance. It was established that the housing subsidy is the main part of Ukrainian social policy, which is 1%-2.5% of GDP in 2016-2021. It was established that in 2020 housing subsidies were directed to the payment of housing and communal services to 2,660,659 households, and housing subsidies in the form of cash were directed to reimbursement of costs for the purchase of liquefied gas, solid and liquid stove fuel for 384,674 households. It was determined that in 2020, the total amount of assigned housing subsidies amounted to UAH 25.5 billion, and the average amount of assigned housing subsidies to reimburse the costs of paying for housing and communal services was UAH 1,615.39. It has been established that all restrictions on the property status of households applying for housing subsidies, except for one-time expensive purchases (over UAH 50,000), will be abolished. It was determined that due to the conditions of martial law in Ukraine, the criteria and conditions for providing housing subsidies have not changed, however, certain changes have been implemented in the administration system: if until recently the functions of providing housing subsidies were implemented by local social protection bodies, now at individual stages these functions are acquired by the Pension Fund. As a result of the conducted research, we consider it necessary to implement the following measures in the social sphere: to increase the effectiveness of the mechanisms of social ordering and control over the quality of the provision of social services to citizens and households; to improve, form and implement appropriate state standards in the field of social services provision.
Keywords: housing subsidy; tool; financial assistance; population